Because of Madeline - Stolz, Mary 1920- (New York Harper, 1957)
A nineteen-year-old girl reflects on the winter she was fourteen, when a coarse, hostile, brilliant daughter of a cleaning woman began to attend her select private school, and on the effect knowing Madeline had on her idealistic older brother, her own priggishness and conformity, and others at the school.